Migration and maternal health: experiences of brazilian women in Portugal - Ligia Moreira Almeida; Jose Peixoto Caldas (Instituto Materno Infantil de Pernambuco, 2013)
OBJECTIVES: to characterize maternal and neonatal healthcare provided to Brazilian population, assessing key factors: access, use and quality of care received during this period. The goal was to assess possible differences regarding women's perceptions regarding the quality and appropriateness of care received, providing qualitative information, as part of a holistic perspective. METHODS: the present study adopted a qualitative methodology (semi-structured interviews) for collecting and analyzing data. Possible differences in women's perceptions regarding the quality and appropriateness of care received were assessed, providing qualitative information, as part of a holistic perspective. The present study was based on privileged information obtained from Brazilian women, residing in the metropolitan area of Porto, regardless of their legal status. RESULTS: a certain dissatisfaction emerged among Brazilian women regarding the quality of information provided by health professionals, the communications skills of these professionals, in addition to a perception of reduced access to medical specialties, especially in primary care. Misinformation about legal rights and inappropriate clarification during medical appointments were frequently reported and interacted with social determinants to result in poorer medical care. CONCLUSIONS: special attention should be given to the specific needs and understanding of immigrants during pregnancy and motherhood in order to improve healthcare. New challenges tend to lie not only in ensuring access, but mostly in promoting equity, as away of providing high-quality care for all.